Características físicas, somatotipo e desempenho de corredores de 100 e 400 metros no Rio Grande do Norte - Figueiredo, José dos Santos (2012)
Objective: The aim of the study was to investigate physical characteristics and to examine association between somatotype and performance in collegiate runners of 100 m and 400 m. Methods: The sample, male runners (n=39) competing at the regional level in the state of Rio Grande do Norte, Brazil, had height, body mass, skinfolds, limb circumference and skeletal breadths measured. Then, the somatotype was calculated by Health-Carter method. Races (100 m and 400 m) were held to assess athletic performance. Descriptive statistics were calculated for the total sample, as well as for the 100 m and 400 m groups, and established four subgroups, named quartiles. For analysis between groups of runners (100 m x 400 m) was used Student's t test for independent samples. To examine the relationship between the race times and anthropometric variables, was used the Pearson correlation test. The somatotype dispersion distance and somatotype spatial distance were calculated among subgroups. One-way analysis of variance, the Wilcoxon test followed of Tukey post test, and correlation analysis were used with a significance level of p<0.05. Results: Somatotype with mesomorphy and ectomorphy dominance was exhibited by 100 m and 400 m athletes. Endomorphy was low in both groups, especially in 400m runners, who had more elongated body types than 100 m runners. When separately compared by athletic performance quartile, 100 m sprinters of better qualifications (G100-G1) had somatotype with dominant mesomorphy, whereas 400 m runners had somatotype with dominant ectomorphy. A significant correlation (r = -0.55, p=0.008) between calf circumference and 100 m race times was observed showing the importance of muscularity, whereas a significant correlation was found between height and 400 m race times (r = -0.53, p=0.02) showing the importance of linearity. Conclusion: Runners of 100 and 400 may show differences in physical characteristics, depending on the level of athletic performance. Anthropometric periodic evaluations may help in the training process of these athletes. However, more specific assessment parameters should be taken into account, because somatotype by itself has not power to predict whether an individual will succeed in racing speed